IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY PT PERTAMINA RU II SUNGAI PAKNING DALAM MEMBANGUN ARBORETUM GAMBUT MARSAWA TAHUN 2020 - Azani Safira; Tito Handoko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The Peat Arboretum Program is the goal of implementing social and environmental responsibility policies. PT Pertamina RU II Sungai Pakning's Corporate Social Responsibility has a long process related to the implementation of social and environmental responsibility. This research was conducted to find out the process of implementing corporate social and environmental responsibility and the success factors that influence the implementation of the Marsawa Peat Arboretum program in 2020 which is carried out by CSR PT Pertamina RU II Sungai Pakning. The method used in this research is descriptive method with qualitative research. The types of research data are primary data and secondary data. This research was conducted in Sungai Pakning City. This study uses the theory of Good Corporate Governance, 5 principles that become aspects of the company to maintain relationships with other stakeholders to run the program. Defining the conceptual State-Owned Enterprises, the concept of Corporate Social Responsibility and the implementation of Good Corporate Governance. Then the theory of Policy Implementation with aspects of communication, attitude/disposition, resources and bureaucratic structure. The results of this study are the successful implementation of the Marsawa peat arboretum program so that it can achieve its goals, namely reducing forest and land fires and restoring peat ecosystems. Seen from the Corporate Social Responsibility of PT Pertamina RU II Sungai Pakning which influences the implementation of the Marsawa peat arboretum program. CSR includes transparency, accountability, responsibility, independence and equality in the CSR of PT Pertamina RU II Sungai Pakning. becomes a variable for the successful implementation of the implemented policies and will achieve the goal of prospering the community, improving the economy, and protecting the surrounding environment. CSR is said to be successful by looking at the aspects of Communication, Resources, Attitudes, Bureaucratic Structure. Keywords :Transparancy, Accountability, Responsibility, Indepedency, Fairness